Overproduction of gentamicin B in industrial strain Micromonospora echinospora CCTCC M 2018898 by cloning of the missing genes genR and genS - Chang, Yingying; Chai, Baozhong; Ding, Yunkun; He, Min; Zheng, Linghui; Teng, Yun; Deng, Zixin; Yu, Yi; Liu, Tiangang (Metabolic engineering communications, 2019)
In pharmaceutical industry, isepamicin is mainly manufactured from gentamicin B, which is produced by Micromonospora echinospora as a minor component of the gentamicin complex. Improvement of gentamicin B production through metabolic engineering is therefore important to satisfy the increasing demand for isepamicin. We hypothesized that gentamicin B was generated from gentamicin JI-20A via deamination of the C2’ amino group. Using kanJ and kanK as the gene probes, we identified the putative deamination-related genes, genR and genS, through genome mining of the gentamicin B producing strain M. echinospora CCTCC M 2018898. Interestingly, genR and genS constitute a gene cassette located approximately 28.7 kb away from the gentamicin gene cluster. Gene knockout of genR and genS almost abolished the production of gentamicin B in the mutant strain, suggesting that these two genes, which are responsible for the last steps in gentamicin B biosynthesis, constitute the missing part of the known gentamicin biosynthetic pathway. Based on these finding, we successfully constructed a gentamicin B high-yielding strain (798 mg/L), in which an overexpression cassette of genR and genS was introduced. Our work fills the missing piece to solve the puzzle of gentamicin B biosynthesis and may inspire future metabolic engineering efforts to generate gentamycin B high-yielding strains that could eventually satisfy the need for industrial manufacturing of isepamicin. •Two missing genes in the biosynthetic pathway of gentamicin B were found.•CRISPR/Cas9 was applied successfully to delete genes in Micromonospora echinospora.•Overexpression of genR/S cassette improved gentamicin B titer by 64% in current industrial strain.